DESAIN DAN ANALISA KERUGIAN SISTEM PLTS ATAP ON-GRID MENGGUNAKAN SOFTWARE PVSYST DI GEDUNG DINAS LINGKUNGAN HIDUP KABUPATEN MALINAU - Fitriani Said; Abil Huda; Priskah Melati (Jurusan Teknik Elektro, Fakultas Teknik, Universitas Borneo Tarakan, 2026)
Current energy demand still largely relies on fossil energy sources such as petroleum, coal, and natural gas. However, the availability of fossil energy is gradually decreasing, thus a transition to renewable energy sources such as solar energy is necessary. PLTSA (Solar Power Plant) is a solar energy-based power generation system. The PLTSA system was designed for the Environmental Agency Office Building of Malinau Regency using PVsyst software with an on-grid system connected to the utility grid (PLN). The DLH building consumes 318 kWh of energy per day. The PLTSA was designed with a capacity of 69.8 kWp using a total of 128 solar modules installed on both sides of the roof, with 65 battery units and 4 inverters. From this design, the PLTSA is capable of producing 127,955 kWh/year. However, due to energy losses of 21.15%, the amount of electricity that actually reaches the user is only 100,886 kWh per year. By utilizing the PLTS, the DLH building can reduce its electricity expenses by up to IDR 112,461,660 per year.